IMPLEMENTASI PROGRAM KESERASIAN SOSIAL BERBASIS MASYARAKAT DI KOTA PALU - Azmi, Azmi (Katalogis, 2017)
The purpose of this research was to find out and explain the inhibiting factors toward the community-based social order program in Palu city. It was investigated by using the policy implementation model by Donald S.Van Metter and Carls E. Van Horn Particulary on the aspect of standard and target, resources, the organizational characteristics of the executors, the attitudes of the executors, the communication within the relevant organizations, and the social, economic, and politic environment. This is a qualitative research in which there were 7 informants taken purposively. The research shows that the community-based social order program in Pengawu and Duyu, palu city, has not been implemented optimally due to the facts that: 1) the standard and target did not run well, 2) the human resources and funding in the implementation of this policy were limited, 3) there was no much support from the community faced by the executors from the man power and social office and the local KSBM forums, 4) the participation of most community members was low, 5) the communication for extending this program was ineffective, 6) the social, economic, and politic environment has affected the implementation of this program and also influenced the cooperation from the community members because there was no incentives in the extension program.